Functional Connectivity of the Amygdala in Early Childhood Onset Depression - Luking, Katherine R. (2011)
OBJECTIVE: Adult major depressive disorder (MDD) is associated with reduced cortico-limbic functional connectivity thought to indicate decreased top-down control of emotion. However, it is unclear whether such connectivity alterations are also present in early childhood onset MDD. METHOD: Fifty-one children ages 7–11 years, prospectively studied since preschool age, completed resting state fMRI and were assigned to four groups: 1) C-MDD (N=13) personal history of early childhood onset MDD; 2) M-MDD (N=11) a maternal history of affective disorders; 3) CM-MDD (N=13) both maternal and early childhood onset MDD or 4) CON (N=14) without either a personal or maternal history. We used seed-based resting state functional connectivity (rsfcMRI) analysis in an independent sample of adults to identify networks showing both positive (e.g., limbic regions) and negative (e.g., dorsal frontal/parietal regions) connectivity with the amygdala. These regions were then used in ROI based analyses of our child sample. RESULTS: We found a significant interaction between maternal affective disorder history and the child's MDD history for both positive and negative rsfcMRI networks. Specifically, when copared to CON, we found reduced connectivity between the amygdala and the “Negative Network” in children with C-MDD, M-MDD and CM-MDD. Children with either C-MDD or a maternal history of MDD (but not CM-MDD) displayed reduced connectivity between the amygdala and the “Positive Network”. CONCLUSIONS: Our finding of an attenuated relationship between the amygdala, a region affected in MDD and involved in emotion processing, and cognitive control regions is consistent with a hypothesis of altered regulation of emotional processing in C-MDD suggesting developmental continuity of this alteration into early childhood.